The life of wisdom in Rousseau's Reveries of the solitary walker - Pangle, Thomas L. (Cornell University Press, 2023)
""The first complete exegesis and interpretation of Rousseau's final and culminating work, showing its full philosophic and moral teaching. Reveries of a Solitary Walker is Rousseau's most profound exploration and articulation of his own life, personality, soul, and thought as 'the man of nature enlightened by reason'"--Provided by publisher"--